STRATEGI PEMERINTAH DALAM UPAYA PEMBERDAYAAN MASYARAKAT PADA DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN MALANG TAHUN 2022 - Fransiskus Wonda Mete; Cahyo Sasmito; Eri Yusnita (The Juris, 2023)
This research was conducted to find out the Government's programs and strategies in community empowerment efforts, at the community and village empowerment offices in Malang Regency, in accordance with the mandate of Law Number 23 of 2014 concerning Regional Government. Regional Government is the administration of government affairs by the regional government and regional people's representative councils according to the principle of autonomy and co-administration with the principle of broadest autonomy. This research was conducted at the community empowerment service and Malang district villages using qualitative descriptive. The determination of informants was carried out using a porposive sampling technique and then the data found was analyzed by reducing data, presenting data and drawing conclusions. The results of this study show that the government's strategy in community empowerment efforts at the community empowerment service and Malang district villages as a whole has been running effectively. But there needs to be continuous improvement so that what the government hopes for can be realized. The supporting factor is the existence of good cooperation between the village apparatus and the community itself.